A preliminary study on ultrasound-guided percutaneous microwave ablation for palliative treatment of advanced head and neck malignancies. (1st January 2021) - Liao, Jifen; Lu, Man; Wu, Xiaobo; Wang, Lu; Li, Tingting; Tang, Yihan; Zou, Jie; Pu, Wei
Abstract: Objective: To evaluate the safety and efficacy of ultrasound (US)-guided percutaneous microwave ablation (UgPMWA) for palliative treatment of advanced head and neck malignancies. Materials and methods: This study includes 18 consecutive patients with advanced head and neck malignancies ( n = 24), who have undergone UgPMWA for palliative treatment at our institution from December 2016 to April 2020. The maximum diameter and volume of the tumor were assessed by US, CT or MRI before microwave ablation (MWA), 1, 3 and 6 months after MWA and every 6 months thereafter. The quality of life was clinically assessed by the University of Washington Head and Neck Quality of Life questionnaire (UW-QOl). Results: The success rate of tumor-targeting microwave antenna placement was 100%. No nerve injury and serious complications or death occurred during the perioperative period. The follow-up duration varied from 1 month to 38 months (11.56 ± 10.23 months) among patients. By the last follow-up before submission, the value of maximum diameter (5.00 ± 2.90 vs 3.28 ± 2.11 cm. p < 0.05) and tumor volume decreased significantly（74.35 ± 46.88 vs 47.45 ± 24.08 cm 3 . p < 0.05）respectively after palliative treatment with UgPMWA. UW-QOl of the patients was improved (59.24 ± 11.51 vs 69.84 ± 8.12, p < 0.05). Conclusion: UgPMWA is safe and effective for the palliative treatment of head and neck malignancies. Ultrasonic guidance can indicate an accurate location of the microwave antenna. It can also monitor the ablation area in real-time during the operation to avoid damage to surrounding normal tissues.